The Responsibility of Islamic Education (Syara’ Verses Review) - Syarifatul Marwiyah (FALASIFA : Jurnal Studi Keislaman, 2022)
Abstract Every son of Adam has responsibility for himself as well as those for whom he is responsible. Especially for educators who are responsible for Islamic education for their students. The responsibility of Islamic education is broad and detailed, not only about spiritual education, and physical education but also getting more attention. Therefore, it is very important to know what responsibility that educators should fulfill for each student to be accepted by them. This article aims to describe how the responsibility of Islamic education is strengthened by syara' verses so that there is no doubt about carrying out these responsibilities. Every educator must fulfill his Islamic education responsibilities, both in terms of faith, character, physical, intellectual, social, and sexual education to realize an individual who has good behavior according to Islam.